Levothyroxine Therapy in Thyrodectomized Patients - Miccoli, Paolo; Materazzi, Gabriele; Rossi, Leonardo (Frontiers in Endocrinology, 2021)
Administration of the optimal dose of levothyroxine (LT4) is crucial to restore euthyroidism after total thyroidectomy. An insufficient or excessive dosage may result in hypothyroidism or thyrotoxicosis, either one associated with a number of symptoms/complications. Most literature regarding the LT4 dosage deals with the treatment of primary hypothyroidism, whereas a limited number of studies handle the issue of thyroxin replacement after total thyroidectomy. A literature review was performed focusing on all papers dealing with this topic within the last 15 years. Papers that reported a scheme to calculate the proper LT4 dose were collected and compared to set up a review exploring limits and drawbacks of LT4 replacement therapy in the wide population of patients who had undergone thyroidectomy. Most of the methods for monitoring and adjusting thyroid hormone replacement after thyroidectomy for benign disease use LT4 at an empirical dose of approximately 1.6 μg/kg, with subsequent changes according to thyroid function test results and assessments of the patient’s symptoms. Approximately 75% of patients require a dose adjustment, suggesting that factors other than body weight play a role in the determination of the proper LT4 dose. Hence, several schemes are reported in the literature for the proper initial dose of LT4. An inadequate level of thyroid hormone levels in these patients can be due to several factors. The most common ones that lead to the necessity of LT4 dose adjustments include lack of compliance, changes in LT4 formulation, dosage errors, increased serum levels of T4-binding globulin, body mass changes, and dietary habits. Moreover, concomitant ingestion of calcium supplements, ferrous sulfate, proton-pump inhibitors, bile acid sequestrants, and sucralfate might influence LT4 absorption and/or metabolism. Furthermore, some gastrointestinal conditions and their treatments can contribute to suboptimal LT4 performance by altering gastric acidity and thereby reducing its bioavailability, particularly in the solid form. Beyond the classic tablet form, new formulations of LT4, such as a soft gel capsule and an oral solution, recently became available. The liquid formulation is supposed to overcome the food and beverages interference with absorption of LT4 tablets.